2016
DOI: 10.1103/physrevb.94.075142
|View full text |Cite
|
Sign up to set email alerts
|

Perfect control of reflection and refraction using spatially dispersive metasurfaces

Abstract: Non-uniform metasurfaces (electrically thin composite layers) can be used for shaping refracted and reflected electromagnetic waves. However, known design approaches based on the generalized refraction and reflection laws do not allow realization of perfectly performing devices: there are always some parasitic reflections into undesired directions. In this paper we introduce and discuss a general approach to the synthesis of metasurfaces for full control of transmitted and reflected plane waves and show that p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
396
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 480 publications
(426 citation statements)
references
References 55 publications
11
396
0
Order By: Relevance
“…For this purpose, we use a synthesis method based on generalized Snell's laws which intuitively allows for arbitrary control of reflected and transmitted waves through local phase shifts at the metasurface. It should be mentioned that this synthesize method suffers in terms of power efficiency due to spurious scattering and it has been recently found that the ideal required phase shift differs from the prescription of the generalized Snell's law [77][78][79]. However, due to the 2π phase span provided by the proposed design paradigm, it can be used flexibly in more sophisticated synthesis methods to improve the efficiency of functionality.…”
Section: Wavefront Engineering Of Generated Frequency Harmonicsmentioning
confidence: 99%
“…For this purpose, we use a synthesis method based on generalized Snell's laws which intuitively allows for arbitrary control of reflected and transmitted waves through local phase shifts at the metasurface. It should be mentioned that this synthesize method suffers in terms of power efficiency due to spurious scattering and it has been recently found that the ideal required phase shift differs from the prescription of the generalized Snell's law [77][78][79]. However, due to the 2π phase span provided by the proposed design paradigm, it can be used flexibly in more sophisticated synthesis methods to improve the efficiency of functionality.…”
Section: Wavefront Engineering Of Generated Frequency Harmonicsmentioning
confidence: 99%
“…Physically, this limitation also stems from the local impedance mismatch on the metasurface, which remains intact for polarization preserved reflection. In general, i.e., for refracting metasurfaces and/or polarization conversion, bianisotropy may relax the local amplitude modulation along the surface [35,36]. It follows that the only way to keep a unitary conversion efficiency towards the desired direction with a steering ultrathin metasurface is to locally absorb and pump a portion of the incident power in different regions within the superlattice (equivalent to nonlocal operation).…”
Section: Beam Steering With Metasurfacesmentioning
confidence: 99%
“…An intelligent reflecting surface (IRS) is a thin two-dimensional metamaterial (i.e., engineered material) that can control and transform electromagnetic waves [1,2]. It has been demonstrated experimentally that metasurfaces can dynamically produce unusual scattering, polarization, and focusing properties to obtain desired radiation patterns [3,4].…”
Section: Introductionmentioning
confidence: 99%